Serum inflammatory cytokines and depression in coronary artery disease - Tajfard, Mohammad; Abd Latiff , Latiffah; Rahimi, Hamid Reza; Mouhebati, Mohsen; Esmaeily, Habibollah; Taghipour, Ali; Mahdipour, Elahe; Davari, Hafezeh; Saghiri, Zahra; Hanachi, Parichehr; Mobarhan, Majid Ghayour; Ferns, Gordon A.; et al. (Iranian Red Crescent Hospital of Dubai, 2014)
Background: Severe depression may be accompanied by immune dysregulation and is also associated with increased risk of coronary artery disease (CAD).